Humanized Biomimetic Nanovesicles for Neuron Targeting. Issue 19 (11th August 2021) - Zinger, Assaf; Cvetkovic, Caroline; Sushnitha, Manuela; Naoi, Tomoyuki; Baudo, Gherardo; Anderson, Morgan; Shetty, Arya; Basu, Nupur; Covello, Jennifer; Tasciotti, Ennio; Amit, Moran; Xie, Tongxin; et al.
Abstract: Nanovesicles (NVs) are emerging as innovative, theranostic tools for cargo delivery. Recently, surface engineering of NVs with membrane proteins from specific cell types has been shown to improve the biocompatibility of NVs and enable the integration of functional attributes. However, this type of biomimetic approach has not yet been explored using human neural cells for applications within the nervous system. Here, this paper optimizes and validates the scalable and reproducible production of two types of neuron‐targeting NVs, each with a distinct lipid formulation backbone suited to potential therapeutic cargo, by integrating membrane proteins that are unbiasedly sourced from human pluripotent stem‐cell‐derived neurons. The results establish that both endogenous and genetically engineered cell‐derived proteins effectively transfer to NVs without disruption of their physicochemical properties. NVs with neuron‐derived membrane proteins exhibit enhanced neuronal association and uptake compared to bare NVs. Viability of 3D neural sphere cultures is not disrupted by treatment, which verifies the utility of organoid‐based approaches as NV testing platforms. Finally, these results confirm cellular association and uptake of the biomimetic humanized NVs to neurons within rodent cranial nerves. In summary, the customizable NVs reported here enable next‐generation functionalized theranostics aimed to promote neuroregeneration. Abstract : Membrane proteins are extracted from either human pluripotent stem cells or differentiated neurons and combined with lipids to synthesize biomimetic nanovesicles (NVs). Neural targeting of NVs can be evaluated both in vitro using monolayer cultures and 3D organoids and in vivo by direct injection of NVs into murine trigeminal ganglions.